1998
DOI: 10.1074/jbc.273.48.32102
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of Trypanosomatid Endocytosis Pathways Revealed by Rab4 and Rab5 Isoforms in Trypanosoma brucei

Abstract: Small G proteins of the Rab family are responsible for vesicle fusion and control flux during intracellular transport. Rab5 is important in endosome maturation and Rab4 in recycling of endocytic material. Three Rab5 isoforms identified so far in mammals and three in the yeast genome suggest that conservation of multiple Rab5 isoforms is required for sophisticated regulation of endocytosis. Trypanosoma brucei homologues of Rab5 and Rab4 (TbRab5A and TbRab4) have been identified. Here we report cloning of a seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 38 publications
3
66
0
2
Order By: Relevance
“…This is in good contrast to the yeast and mammalian counterparts, which are virtually interchangeable; Ypt51p expressed in a mammalian cell was properly localized to endosomes and accelerated endocytosis (6). Fifth, compared with other organisms including mammals, plants, yeasts, and a parasitic protist Trypanosoma brucei, which have been shown to possess 2-5 Rab5 isotypes with distinct tissue and organelle distribution or developmental stage-specific expression (46,(57)(58)(59), E. histolytica possesses only a single Rab5 gene based on our thorough search of the genome data base (data not shown). Altogether, EhRab5 represents a unique Rab5 showing diverse localization and functions.…”
Section: Discussionmentioning
confidence: 99%
“…This is in good contrast to the yeast and mammalian counterparts, which are virtually interchangeable; Ypt51p expressed in a mammalian cell was properly localized to endosomes and accelerated endocytosis (6). Fifth, compared with other organisms including mammals, plants, yeasts, and a parasitic protist Trypanosoma brucei, which have been shown to possess 2-5 Rab5 isotypes with distinct tissue and organelle distribution or developmental stage-specific expression (46,(57)(58)(59), E. histolytica possesses only a single Rab5 gene based on our thorough search of the genome data base (data not shown). Altogether, EhRab5 represents a unique Rab5 showing diverse localization and functions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the location of T. brucei Rab28 was consistent with association with one or more of these compartments, especially the endosomes and lysosome (Field et al, 1998;Jeffries et al, 2001;Gabernet-Castello et al, 2009;Leung et al, 2008;Alexander et al, 2002).…”
Section: Subcellular Location Of T Brucei Rab28mentioning
confidence: 99%
“…Rab 5 paralogues in yeast also appear to possess distinct functions, although some redundancy likely exists (40), and similarly nonredundant functionality has been described for mammalian Rab 5 isoforms (41). Previous phylogenetic analyses of Rab 5 paralogues from these three taxa suggested that the last common ancestor of this gene in trypanosomes, yeast, and humans are derived from a single Rab5 gene that was then duplicated in these lineages (42). However, the analysis did not encompass diverse eukaryotic taxa or use methods accounting for rate variation, an important factor that can cause artifacts in phylogenetic reconstruction (31).…”
Section: Evolution Of Early Endosomal Rabs (Rab 5)mentioning
confidence: 99%